Actinidia chlorotic ringspot‐associated virus: a novel emaravirus infecting kiwifruit plants - Zheng, Yazhou; Navarro, Beatriz; Wang, Guoping; Wang, Yanxiang; Yang, Zuokun; Xu, Wenxing; Zhu, Chenxi; Wang, Liping; Serio, Francesco Di; Hong, Ni (Molecular plant pathology, 2017)
Summary By integrating next‐generation sequencing (NGS), bioinformatics, electron microscopy and conventional molecular biology tools, a new virus infecting kiwifruit vines has been identified and characterized. Being associated with double‐membrane‐bound bodies in infected tissues and having a genome composed of RNA segments, each one containing a single open reading frame in negative polarity, this virus shows the typical features of members of the genus Emaravirus. Five genomic RNA segments were identified. Additional molecular signatures in the viral RNAs and in the proteins they encode, together with data from phylogenetic analyses, support the proposal of creating a new species in the genus Emaravirus to classify the novel virus, which is tentatively named Actinidia chlorotic ringspot‐associated virus (AcCRaV). Bioassays showed that AcCRaV is mechanically transmissible to Nicotiana benthamiana plants which, in turn, may develop chlorotic spots and ringspots. Field surveys disclosed the presence of AcCRaV in four different species of kiwifruit vines in five different provinces of central and western China, and support the association of the novel virus with symptoms of leaf chlorotic ringspots in Actinidia. Data on the molecular features of small RNAs of 21–24 nucleotides, derived from AcCRaV RNAs targeted by host RNA silencing mechanisms, are also reported, and possible molecular pathways involved in their biogenesis are discussed.